Procedural Learning, Grammar, and Motor Skills in Children With Childhood Apraxia of Speech, Speech Sound Disorder, and Typically Developing Speech. - Iuzzini-Seigel, Jenya (Journal of Speech, Language & Hearing Research, 2021)
Purpose:This case–control study sought to determine if(a) children with childhood apraxia of speech (CAS), other speech sound disorders (SSDs), and typical development would perform differently on a procedural learning assessment and (b) whether grammatical ability would impact group differences.Method:Communication, motor, and procedural learning abilities were assessed in 48 children with CAS (n= 13), SSD (n= 20), and typical development (n= 15), between 43 and 97 months of age (M= 66 months, SD= 12 months). Results: On average, children with CAS demonstrated grammatical and motor impairments and required an increased number of exposures to the visuo spatial sequence to demonstrate procedural learning, compared to peers with SSD or typical development. A subset of children from each group demonstrated an unanticipated procedural learning pattern wherein they evidenced an uptick in reaction time during the second sequenced block. Children with CAS with this pattern still evidenced procedural learning gains by the fifth sequenced block. In contrast, children with SSD and typical development with this pattern showed poor procedural learning outcomes and were characterized by lower scores on language and motor assessments as well.Conclusions:This research provides partial support for the procedural learning deficit hypothesis in children with CAS and for a subset of children with SSD as well. Future research should examine the role of a serial reaction time task in identifying children at risk of multisystem communication and motor deficits.